The Urgency Of The Organization And Legitimacy Of The Digitalization Of The General Meetings Of Shareholders Of The Limited Liability Company During The Covid-19 Time In Review Of The Ius Constitutum (Journal of Private and Commercial Law, 2022)
Limited Liability Company is a legal entity of capital partnership that is engaged in business with authorized capital which is fully divided through shares. The purpose of a limited liability company is to run a business with capital divided into shares in which the shareholders have a stake in carrying out legal actions without being responsible for themselves regarding agreements in the company. One of the organs in a limited liability company that also has an important role is the General Meeting of Shareholders. Oftentimes, the General Meeting of Shareholders is crowned as the most vital organ of a limited liability company because it has the authority that other limited company organs do not have, such as the Board of Directors and the Board of Commissioners. The rapid development of Covid-19 has hampered the holding of the GMS which was previously carried out in person but has now become virtual via teleconference media due to the physical distancing policy. Article 77 Paragraph 1 of Law Number 40 of the Year 2007 and POJK Number 16/POJK.04/2020 is a breakthrough to accommodate the online General Meeting of Shareholders of Limited Liability Companies. Based on this description, this research is aimed at knowing and analyzing the new arrangements for the General Meeting of Shareholders in Limited Liability Companies, especially in its implementation after Covid-19 hit Indonesia. The research method used is normative juridical law research, namely by collecting secondary legal data consisting of secondary and primary legal materials. Data collection techniques are carried out by studying facts, documents, and books related to the problems studied. The implementation of the digitization of the GMS can generally be carried out either through teleconference media, video conferences, or other electronic media that allows all participants to interact and participate efficiently in meetings.